Inflation und Schuldenabbau - Thomas Straubhaar; Henning Vöpel; Gerhard Illing; Heiner Flassbeck; Friederike Spiecker; Stefan Bach; Gert G. Wagner (Wirtschaftsdienst, 2012)
Die Rettungsaktionen der EZB stehen in der Kritik: Es wird befürchtet, dass sie zu steigenden Inflationsraten führen könnten. Die Autoren des Zeitgesprächs sehen diese Gefahr nicht. Vielmehr könne ein gemäßigter Anstieg der Inflation sogar dazu beitragen, die Staatsschulden schneller abzubauen. Die Autoren aus dem DIW sehen hier allerdings die Wiedereinführung der Vermögensteuer und eine einmalige Vermögensabgabe als eine gerechtere und transparentere Alternative an. – – The European Central Bank (ECB) recently announced its willingness to do whatever is needed to save the euro. This has raised the question whether such a role of the ECB must lead to higher rates of inflation. Under current recessive macroeconomic conditions in the eurozone, the ECB's expansionary monetary policy will not lead to higher inflation. On the contrary, there is a serious danger of deflation. Higher inflation would likely occur only if a permanent stabilisation function were assigned to the ECB. Yet historical examples show that mistakes can be made. During the stagnation in Japan, US economists heavily criticised the Bank of Japan's timid monetary policy response. But in some sense, current Fed policy seems to be a direct copy of that strategy, caused by uncertainty about the proper communication channel. An inflation tax could help to bring down the mounting public debt in the wake of the financial crisis, but higher wealth taxes have more transparent distributional effects.
Keywords: E31; E42; E50; 330; Geldpolitik; Wirkungsanalyse; Inflation; Haushaltskonsolidierung; EU-Staaten